Assessment of homogeneous electro-Fenton process coupled with microbial fuel cell utilizing Serratia sp. AC-11 for glyphosate degradation in aqueous phase - Oliveira, Weverton V.; Silva, Mércia C.F.; Araújo, Bruno R.; Romão, Luciane P.C. [UNESP] (Elsevier, 2024)
Glyphosate (GLY), a globally-used organophosphate herbicide, is frequently detected in various environmental matrices, including water, prompting significant attention due to its persistence and potential ecological impacts. In light of this environmental concern, innovative remediation strategies are warranted. This study utilized Serratia sp. AC-11 isolated from a tropical peatland as a biocatalyst in a microbial fuel cell (MFC) coupled with a homogeneous electron-Fenton (EF) process to degrade glyphosate in aqueous medium. After coupling the processes with a resistance of 100 Ω, an output voltage value of 0.64 V was obtained and maintained stable throughout the experiment. A bacterial biofilm of Serratia sp. AC-11 was formed on the carbon felt electrode, confirmed by attenuated total reflectance-Fourier transformed infrared (ATR-FTIR) and scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS). In the anodic chamber, the GLY biodegradation rate was 100% after 48 h of experimentation, with aminomethylphosphonic acid (AMPA) remaining in the solution. In the cathodic chamber, the GLY degradation rate for the EF process was 69.5% after 48 h experimentation, with almost all of the AMPA degraded by the in situ generated hydroxyl radicals. In conclusion, the results demonstrated that Serratia sp. AC-11 not only catalyzed the biodegradation of glyphosate but also facilitated the generation of electrons for subsequent transfer to initiate the EF reaction to degrade glyphosate. This dual functionality emphasizes the unique capabilities of Serratia sp. AC-11, it as an electrogenic microorganism with application in innovative bioelectrochemical processes, and highlighting its role in sustainable strategies for environmental remediation.
Keywords: Biodegradation; Electro-fenton; Glyphosate; Microbial fuel cell; Serratia sp. AC-11